Eksaminasi Keabsahan Penggeledahan dan Penyitaan dalam Praperadilan: Rekonstruksi Kewenangan dengan Pendekatan Plain View Doctrine - Erwin Susilo; Dharma Setiawan Negara; Muhammad Rafi (CV Rewang Rencang, 2025)
Pretrial motion in Indonesia, inspired by the principle of habeas corpus, has the authority to test the legality of law enforcement actions, including searches and seizures. However, this mechanism is *post-factum* and limited to formal aspects, such as the completeness of the warrant, without assessing the material requirements that determine the legality of the action. This limitation has the potential to cause injustice, especially in cases of urgent searches and seizures, where officers often act without prior court permission. This study aims to reconstruct the authority of pretrial motion by integrating the Plain View Doctrine (PVD), a doctrine from the common law system that allows the seizure of evidence without a warrant if it meets three requirements: (1) officers are legally present at the location, (2) the evidence is clearly visible (immediately apparent), and (3) there is a probable cause that connects the object to the crime. The research method used is normative juridical with a conceptual and statutory approach. The results of the study indicate that the application of PVD can strengthen the pretrial control function by expanding the scope of testing from merely formal to substantial aspects. In addition, this study proposes the optimization of digital systems such as *E-Berpadu* to accelerate the licensing process in urgent circumstances. Thus, the reconstruction of pretrial authority based on PVD is expected to ensure a balance between the effectiveness of law enforcement and the protection of human rights.